PRELIMINARY STUDY OF ELASTICITY ON BINARY ALLOY - Pramono, Andika Widya; Suryantoro, Anton (Jurnal Metalurgi, 2011)
If the components of the mixture have different elastic moduli or different lattice structures, elastic effects might influence the rate of coarsening and the morphology of the particles. In this case the aspect of quasi-static equilibrium for the mechanical part is more predominant than the diffusion mechanism. The resulting elastic effects have a pronounced impact on the evolving coarsening morphology and hence on the material properties. This paper tries to give preliminary consideration on how this elastic behavior is analyzed through finite element approximation using Cahn Hiliard Approach followed by Fourth Order Nonlinear Degenerate Parabolic Equation. Cahn–Hilliard model with elastic contributions is based on a Ginzburg–Landau free energy which is a functional in terms of the concentration difference.